2005
DOI: 10.1097/00004872-200501000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Temporal renal expression of angiogenic growth factors and their receptors in experimental diabetes

Abstract: In experimental diabetes, there is significant upregulation within the kidney of various angiogenic cytokines and their receptors. Furthermore, the effects of angiotensin II receptor blockade on these parameters is consistent with the VEGF-VEGF-R2 and angiopoietin-Tie-2 axes being modulated in the kidney by haemodynamic factors in the diabetic context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
61
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 47 publications
6
61
0
1
Order By: Relevance
“…We also assessed ANGPT expression in isolated glomeruli obtained from diabetic patients and living donors. Similar to previous observations in rodents with long-term diabetes duration, [8][9][10] analysis of human glomeruli showed a significant (but modest) imbalance in favor of ANGPT2 in patients with DN compared with control live donor kidney glomeruli; in contrast to our animal model and other studies, 9 Angpt1 did not change. The most likely explanation for this is that our murine experiments examine early stages of diabetic glomerular disease, where angiogenesis is important.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also assessed ANGPT expression in isolated glomeruli obtained from diabetic patients and living donors. Similar to previous observations in rodents with long-term diabetes duration, [8][9][10] analysis of human glomeruli showed a significant (but modest) imbalance in favor of ANGPT2 in patients with DN compared with control live donor kidney glomeruli; in contrast to our animal model and other studies, 9 Angpt1 did not change. The most likely explanation for this is that our murine experiments examine early stages of diabetic glomerular disease, where angiogenesis is important.…”
Section: Discussionsupporting
confidence: 90%
“…7,8 Several reports have suggested that DN kidneys have altered expression of VEGF-A, Angpt1, and also Angpt2, the natural antagonist of Angpt1. [8][9][10] In diabetic mice, deletion of podocyte Angpt1, 8 or further overexpression of VEGF-A in podocytes, worsens glomerular morphology and enhances proteinuria. 11 Viral delivery of COMPAngpt1 12 or either glomerular transgenic or systemic overexpression of sVEGFR1 ameliorates albuminuria in DN.…”
mentioning
confidence: 99%
“…In contrast, glomerular VEGF immunostaining increased to a similar extent in both female and male diabetic animals. The increase in glomerular VEGF may promote glomerular permeability, which would contribute to the increased proteinuria and angiotensinogen excretion in the female and male diabetic animals (36,42). The extent of collagen staining was higher in the males, but was not different between the control and diabetic groups of either sex.…”
Section: Discussionmentioning
confidence: 93%
“…For example, VEGF is closely linked to the increased glomerular permeability seen in diabetes, and this appears to be partly mediated by the AT1 receptor subtype [27]. Furthermore, the pro-sclerotic growth factor CTGF has been reported to play a role in renal fibrosis in diabetic Apoe KO mice [28].…”
Section: Discussionmentioning
confidence: 99%